Exploring the trade (policy) narratives in economic elite discourse - Matthias Aistleitner; Stephan Pühringer (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2020)
Trade liberalization during the neoliberal era since the 1980s has been on the political agenda of many countries. However, in recent years and especially in the course of rising populist movements, protectionist measures seem to be gaining importance again. Nationalist economic policies challenge the overly positive view on economic integration and the reduction of trade barriers established by standard economic theory. In contrast to politicians, for quite a long time the great majority of economists explicitly publicly supported trade liberalization policies. In this paper, we show how trade and trade related policies are addressed and framed in professional economic discourses. Thus, we follow a mixed-method-approach and combine quantitative textual analysis with critical discourse analysis to highlight dominant narratives and imaginaries present in these debates. By analyzing more than 400 trade-related research articles published in high-impact economic journals we highlight three core trade narratives which constitute the elite economists trade discourse: First, "free trade cheerleading" describes a clear link between the alleged lopsidedness of economists in favoring free trade (policies) in the public and academic debate. Second, "Ignorance in a world full of nails" relates to particular methodological and conceptual leanings in the profession, which seem to deepen the dominance of an overall positive evaluation of trade. And third, "success breeds exporting breeds success" postulates a positive causal relation between a firm's economic performance and its export orientation. We conclude that the narrow perspective in economic elite debates prevents a more comprehensive understanding of the multifaceted challenges related to international integration.
Keywords: 330; trade narratives; trade policies; discourse analysis; sociology of economics; textual analysis; top economic journals